2020
DOI: 10.3390/microorganisms8111688
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Borrelia burgdorferi in Stray Dogs from Southern Italy

Abstract: Borrelia burgdorferi is a bacterial pathogen transmitted by Ixodes ticks and is responsible for Lyme disease in both humans and dogs. The aim of this work was to evaluate B. burgdorferi diffusion among stray dogs in Palermo (Sicily, Italy) by serological methods in order to study the risk factors associated with the infection. Serum and blood samples of 316 dogs were collected from a shelter in Palermo, and were analyzed for the presence of antibodies against B. burgdorferi by indirect immunofluorescence assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
0
8
1
3
Order By: Relevance
“…In contrast, B. burgdorferi ( s.l. ) seroprevalence throughout Italy (83.5%) was higher than that previously reported from central (1.4%) and southern (5.4%-7.8%) regions [ 17 , 24 , 25 ]. These results need to be assessed cautiously given the study limitations (e.g.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In contrast, B. burgdorferi ( s.l. ) seroprevalence throughout Italy (83.5%) was higher than that previously reported from central (1.4%) and southern (5.4%-7.8%) regions [ 17 , 24 , 25 ]. These results need to be assessed cautiously given the study limitations (e.g.…”
Section: Discussioncontrasting
confidence: 57%
“…Similarly, Borrelia burgdorferi ( s.l. ) is a zoonotic TBP reported in dogs from endemic regions, including many European countries such as Serbia, Italy and Croatia [ 11 , 12 , 17 , 18 ]. However, seroprevalence of this bacterium in dogs has been reported to be lower (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strays, as hosts of zoonotic pathogens, could represent a potential threat for human health. In Sicily, a high population of stray dogs in urban and peri urban areas is present [ 19 ], and this represents a known but yet underestimated problem [ 20 ]. Official data on the free-roaming stray population is not available.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of public health [28], it is important to understand that dogs can be affected by over 100 zoonotic, bacterial [29], viral [30], and parasitic diseases [31][32][33] and may be carriers of diseases that include rabies [34][35][36][37], leptospirosis [38], hookworm disease, echinococcosis, leishmaniasis [39], ehrlichiosis, anaplasmosis, brucellosis [40], dirofilariasis [41], Bartonella spp. [42], cestodiasis, salmonellosis, campylobacteriosis, yersiniosis, helicobacter, Bordetella pertussis, Borrelia burgdorferi [43], and streptococcus, as well as staph infections, chlamydia, and scabies, among others [44,45]. Diseases like rabies exhibit a huge impact in some countries in Asia (China, India) and Africa, wherein studies identified 55,000 human deaths annually as a consequence of this disease.…”
Section: Introductionmentioning
confidence: 99%